Comparison of APF and STATCOM for Current Harmonic Mitigation (ELEKTRIKA- Journal of Electrical Engineering, 2023)
The application of solid-state electronic devices has recorded a geometric increase in the last decade. Devices such as battery charging systems, inverters, switch mode power supplies and a host of electronic-based devices referred to as non-linear loads distort the source signal (particularly the current). Harmonics distortion imposes a severe impact on the well-being of the power system. They cause excessive device heating, reduced performance efficiency, early insulation failure, decreased dynamic torque in rotating systems, etc. This paper bases a study on Active Power Filter (APF) and Static Synchronous Compensator (STATCOM) for mitigation of these distortive harmonics in a system of 3-phase 11kV/400V, 400kVA feeding a system of non-linear loads. The study is based on the IEEE519 standard limits for current harmonics measured at the PCC. Therefore, the system short circuit ratio (SCR) is first determined. Using synchronous reference frame and instantaneous reactive power theories, the APF and STATCOM are respectively designed and run using MATLAB/Simulink software. The result analysis is obtained from the FFT signal processing toolbox of the software, and the device’s performances are evaluated based on the set standard. Results from the FFT spectra showed that the model system contains a considerable number of harmonics before filtering. However, when these devices are connected to the system, all higher-order harmonics have been minimized to the least fractions with respect to the standard, with STATCOM giving a comparatively better performance.